Assessment of Trigeminal Neurovascular Con?icts Using 3D FIESTA-C Sequence on a 3T MRI - K S Vedaraju; Saripudi S V N P Manikanta Vijay; Yarramsetti Madhusudana; Sabarinath Eada (Asian Journal of Medical Radiological Research, 2021)
Background: Trigeminal neuralgia is an idiopathic chronic excruciating pain disorder along the distribution of trigeminal nerve. This condition is often sparked by facial movements or by speaking or sensory stimulation of one half of face. The cause of trigeminal neuralgia is primarily idiopathic and is implicated with vascular compression in most of the cases. Secondary trigeminal neuralgia occur due to underlying neurological disease. In this prospective study on patients with primary trigeminal neuralgia, we assessed the role of 3D FIESTA-C (Three-dimensional fast imaging employing steady state acquisition in cycled phases) sequence in detection, localisation and describing various patterns of neurovascular conflict (NVC). Subjects & Methods - This Hospital-based prospective study consists of 30 patients with clinically suspected trigeminal neuralgia, referred to the department of radiodiagnosis, Narayana medical college, Nellore, over a period of 2 years. All the 30 cases were imaged on a 3 tesla MRI scanner with a 3D FIESTA-C sequence. Results - In 30 cases, 18 were females, and 12 were males. The mean age at initial presentation is 53 years. The average duration of symptoms at initial presentation among study subjects in our study is 63 days. On MR imaging, in the 30 cases, Grade I conflict is seen in 17, Grade II conflict is seen in 7 and Grade III conflict is seen in 6 patients. The offending arteries include SCA in 24 cases, AICA in 7 cases, PCA in 1 case and VA in 1 case. Conclusion - The addition of the 3D FIESTA-C sequence in the MR imaging protocol helps in better identification of the cranial nerve anatomy and abnormalities. 3D FIESTA-C images help in depicting the neuroanatomy better before planning for microvascular decompression. Grading this neurovascular compression helps the surgeon in stratifying the patients and their treatment. Imaging evidence of neurovascular conflict must be correlated with clinical symptoms while making the diagnosis.